EFL Student Difficulties of Online Learning During Coronavirus Pandemic at IAIN Langsa - Muslem Muslem (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2021)
This research was aimed to find out the EFL students’ difficulties and psychological impact of online learning during coronavirus (COVID-19 ) at IAIN Langsa. This research used a qualitative approach. Documentation and interview were used to collect the data in this research. The subject of this research was EFL students of the English education department at the sixth-semester students of IAIN Langsa. The result of this research showed that the students encountered several difficulties in learning online consisting of; Internet data, internet connection, difficulties in doing assignments, intrusion, lack of experience in using technology, comprehending the lesson of EFL and interaction between students and lecturer. On the other hand, the psychological impact of online learning encountered by the students such as; frustration and feeling sadness